Is palatal cavity volume affected by maxillary sinus pathologies? A CBCT study - Mediha Erturk; Melek Tassoker; Anıl Didem Aydın Kabakcı (BMC, 2024)
Abstract Aim This study uses cone beam computed tomography (CBCT) to determine whether pathology in the maxillary sinus (MS) affects the volume of the palatal cavity. Methods 188 individuals, 95 women and 93 men, aged between 17 and 63, were included in the study. MS pathology in the patients and the open-closed status of the maxillary sinus ostium (MSO) were recorded. Palatal volume measurements were performed using open-access ITK-SNAP via CBCT images. Statistical analysis of the study was conducted using SPSS v.21 software (IBM. Chicago. IL. USA), and p<0.05 was considered statistically significant. Results The average palatal volume was 1375.29±313.38 mm3 in male patients and 1235.33±250.40 mm3 in females, and it was found to be statistically significant between genders (p=0.001). MS pathology was detected in 114 (60.6%) of the patients. It was determined that the most frequently observed pathology in both the right (n = 58, 30.9%) and left (n = 65, 34.6%) side MS of individuals was mucosal hypertrophy. It was determined that the mean palatal volume was higher when the MSO was closed (p = 0.000). As a result of the correlation analysis, it was shown that the presence of MS pathology had a positive effect in explaining palate volume by 38.6% (R 2 = 0.386). Conclusion Palatal cavity volume was affected by maxillary sinus pathologies. Palatal cavity volume increases in the presence of MS pathologies and when MSOs are closed.